2004
DOI: 10.1038/sj.ijo.0802531
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin is associated with insulin resistance independent of age, body mass index, fat mass, lipids, and pubertal development in nondiabetic adolescents

Abstract: OBJECTIVE:The rising epidemic worldwide in overweight and obese children requires urgent attention. Leptin has been found to be associated with body weight control and possibly affects insulin sensitivity. Since insulin resistance is associated with obesity in adults and possibly in adolescents, we set out to investigate the association of plasma leptin level with various anthropometric indices, body fat mass (FM), lipids, and insulin resistance (IR) index in nondiabetic adolescents. DESIGN: A cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
57
1
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 51 publications
11
57
1
12
Order By: Relevance
“…In obesity, the plasma leptin concentration is elevated and its production depends on the amount of adipose tissue 18) . In general, the plasma leptin level is higher in women than in men 19) and here we found that it was higher in girls than in boys.…”
Section: Discussionmentioning
confidence: 99%
“…In obesity, the plasma leptin concentration is elevated and its production depends on the amount of adipose tissue 18) . In general, the plasma leptin level is higher in women than in men 19) and here we found that it was higher in girls than in boys.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that increased levels of leptin can inhibit the secretion of insulin 31 . In a study on insulin resistance and leptin, conducted with 402 adolescents, and Huang et al 31 found that leptin was positively correlated with central fat distribution and total body fat, with levels of triglycerides and HOMA. The same authors claim that leptin levels have been associated with decreased arterial distensibility, and leptin potent predictor of cardiovascular disease and metabolic syndrome in adolescents.…”
mentioning
confidence: 99%
“…Previous studies have also reported correlation of leptin levels with BMI, BP, WC, TG, IR and UA [17,34,43] . Hyperleptnemia may indicate leptin resistance [33] as well as IR [44] , and it could be a predictor for the development of MetS and CV disease in adulthood. Thus, measurement of leptin levels may be helpful in identifying youths at risk of developing these disorders.…”
Section: Discussionmentioning
confidence: 99%